Mechanical and Structural Correlation of Lateritic Soil Road Base Stabilized with Cement and Selected Biochars - Otieno, Meshack; Kabubo, Charles; Gariy, Zachary (Engineering, Technology & Applied Science Research, 2023)
The study considers the strength and structural characterization of lateritic soil road base in order to increase the strength of low-volume sealed road construction. Sugar Cane Bagasse Ash (SCBA) and Saw Dust Ash (SDA), mixed with soil and in combination with different percentages of Ordinary Portland Cement (OPC), were utilized in the current study. Structural and mechanical characterization of the investigated samples was performed by X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Standard Proctor Test (SPT), Unconfined Compression Strength (UCS) Test, and California Bearing Ratio (CBR) Test. The observed increase in strength may be due to the reduction of mica, quartz, and calcite in the investigated samples. CaO and SiO2 contribute to the development of strength in cement, while SCBA, and SDA-stabilized lateritic soils. The microstructural study revealed that the mica, quartz, and calcite phases play a very important role in maintaining the strength and stability of the investigated samples.